Perlunya Pengawasan Terhadap Kode Etik Dan Perilaku Hakim Konstitusi Dalam Rangka Menjaga Martabat Dan Kehormatannya: The Need For Supervision On Constitutional Court Judges’ Code Of Ethics & Behavior In Order To Uphold Their Dignity And Honor - Ellydar Chaidir; Suparto Suparto (UIR Law Review, 2017)
In the beginning, the external supervision on Constitutional Court Judges’ ethics and behavior was conducted by Judicial Commission. That was in accordance with the stipulation in Law No. 22 of 2004 and Law No. 4 of 2004. Yet the activity of supervision itself has yet to be conducted, due to Constitutional Court Ruling No. 005/PUU-IV/2006, which stated that Constitutional Court Judges are not subject to Judicial Commission’s supervision. Hence, the supervision was conducted internally by Constitutional Court itself. After the issuance of Government Regulation in Lieu of Law (“PERPU”) No. 1 of 2013 on Second Amendment to Law No. 24 of 2003 (Law No. 4 of 2014), the authority of external supervision was once again being held by Judicial Commission. But with Constitutional Court Ruling No. 1-2/PUU-XII/2014, the PERPU was once again being canceled. Hence, the supervision on the judges is conducted internally via the Board of Ethics of the Constitutional Court. In the future, Constitutional Court Judges must be supervised by external body, but without violating their independency as judges. Yet, since Constitutional Court as the interpreter of Constitution once interpret the scope of “judges” in article 24B (1) of 1945 Constitution are limited to the Judge and Supreme Court Justice (Not including Constitutional Court Judge), to be able to conduct an external supervision to them, a revision on article 24B (1) of 1945 Constitution needs to be conducted.